Methods Of Organizing Children's Physical Education In Preschool Educational Organizations (Global Scientific Review, 2026)
This article covers a wide range of forms, methods and content of the organization of physical education of children in preschool educational institutions. The structure of physical activities, their health-improving, educational and educational significance have been scientifically analyzed. It also explains the factors affecting the physical development of children, methods of effectively organizing training, and pedagogical approaches